Stress influence on orthodontic system components under simulated treatment loadings. (October 2020) - Benaissa, Ali; Merdji, Ali; Bendjaballah, Mohamed Z.; Ngan, Peter; Mukdadi, Osama M.
Highlights: Finite element method has been used to quantify the effects of orthodontic loads applied to achieve desired tooth movement. The stresses propagate in the bone regions in proximity to the mini-implant experiencing high intensity values. The highest stress distribution was observed in the cortical bone around the mini-implant anchorage. This study is sought to identify the stress distribution in a simulated orthodontic system to minimize the failure rate of mini-implants and bracket loss during orthodontic treatment. Abstract: Background and objective: Mini-implants have been developed and effectively used by clinicians as anchorage for orthodontic tooth movement. The objective of this study was to elucidate the stress response of orthodontic forces on the periodontal system, bone tissues, mini-implant and the bracket-enamel interface. Methods: Computer tomography images of a commercially available mini-implant, an orthodontic bracket bonded to a central incisor, and jawbone section models were used to reconstruct three dimensional computer models. These models were exported and meshed in an ABAQUS Ⓡ finite-element package. Material properties, multi-segment interactions, boundary and loading conditions were then applied to each component. Finite-element analyses were conducted to elucidate the effect of orthodontic force on the equivalent von Mises stress response within the simulated orthodontic system. Results: The highest stress values in the orthodontic system were predicted at the mini-implant neck, at the interface of the cortical bone, and gradually decreased in the internal apical direction of the miniscrew. On the alveolar bone, the maximum stress values were located in the alveolar cortical bone near the cervical areas of the mini-implant, which is in line with clinical findings of area where bone loss was found post orthodontic tooth treatment. Another peak of von Mises stress response was found in the enamel bracket junction with a maximum up to 186.05 MPa. To ensure good bonding between the enamel and bracket, it is vital to select carefully the type and amount of bonding materials used in the bracket-enamel interface to assure an appropriate load distribution between the teeth and alveolar bone. The results also revealed the significance of the periodontal ligaments, acting as an intermediate cushion element, in the load transfer mechanism. Conclusions: This study is sought to identify the stress response in a simulated orthodontic system to minimize the failure rate of mini-implants and bracket loss during orthodontic treatment.